Basic journalism an ASEAN handbook - Santos, Vergel O.; ASEAN Committee on Culture and Information ([Manila V. O. Santos], 1992)
A handbook designed for learners and new practitioners of English-language journalism in ASEAN, Southeast Asia's predominantly Malay-Chinese community of nations. It attempts to reconcile to native realities the philosophies and traditions on which journalism is founded, and in that context offers specific advice on the range of editorial skills that makes a basically well-rounded newspaper practitioner.
Purpose: "This book is meant mainly for people who wish to be able to communicate news effectively in a language neither they nor their readers are native to. More specifically, it is for learners and new practitioners of English-language journalism in ASEAN, South East Asia's predominantly Malay-Chinese community of nations."
Contents: What is news. Writing. Copy editing. Headlines. Page layout. Features, community weeklies.
Published under the auspices of the Asean Committee on Culture and Information.
Keywords: Journalism -- ASEAN countries -- Handbooks, manuals, etc